MOTIVASI WISATAWAN BERKUNJUNG KE PANTAI INDAH SERGANG DABO SINGKEP - Purwati, Fani; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The research was to analyze the motivations of tourists visiting the Indah Beach of Sergang Dabo Singkep. The study aims to: (1) to know the motivations of tourists visiting the Indah Beach of Sergang Dabo Singkep. (2) to find out the most dominant factor in tourists visiting the Indah Beach of Sergang Dabo Singkep. This research uses descriptive quantitative method to describe the problem in a visit travellers. The sample used in this study is 100 people.Based on the results of the research that has been done, retrieved the motivation of tourists visit to the Indah Beach of Sergang Dabo Singkep is influenced by physical motivation, motivation, motivation fantasy social and cultural motivation. While the most dominant factor in the tourists visit to the Indah Beach of Sergang Dabo Singkep is physical relaxation in the form of motivation, health, comfort and relax.Keywords: Motivation, Motivation Instrinsik and Ekstrinsik, Tourists.